Cost stickiness effect on firm's performance: insights from Malaysia / Maria Kontesa and Rayenda Khresna Brahmana. - Kontesa, Maria; Brahmana, Rayenda Khresna (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2018)
This study examines the relationship between cost stickiness and firm performance for a sample of 315 listed firms in Malaysia over 2010-2014. The estimation model is built based on previous empirical findings and the agency theory. It is tested using panel regression with the fixed effects model while controlling the Heteroskedasticity and autocorrelation problem. The results show the significant role of cost stickiness on firm performance confirming the alignment proposition of the agency theory. Our research further indicates that some of the managers focus on future projects instead of anchoring to past information due to certainfactors such as change in technology used, economis and politics, which is in line with the institutional theory.